2013
DOI: 10.1002/ijc.28255
|View full text |Cite
|
Sign up to set email alerts
|

The metastatic microenvironment: Lung‐derived factors control the viability of neuroblastoma lung metastasis

Abstract: Recent data suggest that the mechanisms determining whether a tumor cell reaching a secondary organ will enter a dormant state, progress toward metastasis, or go through apoptosis are regulated by the microenvironment of the distant organ. In neuroblastoma, 60-70% of children with high-risk disease will ultimately experience relapse due to the presence of micrometastases. The main goal of this study is to evaluate the role of the lung microenvironment in determining the fate of neuroblastoma lung metastases an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 39 publications
(75 reference statements)
1
28
0
Order By: Relevance
“…In children with high-risk NB, pulmonary metastases are crucial for the long-term outcome. In an orthotopic mouse model for human neuroblastoma metastases (Mhh-NB11 and SH-SY5Y), Maman et al 131 showed that lung-derived factors significantly reduced the viability of micro-NB cells by upregulating the expression of pro-apoptotic genes, inducing cell cycle arrest and decreasing ERK and FAK phosphorylation. The authors concluded that further insights into distant organ environment could reveal therapeutic options against NB metastases.…”
Section: Clinical Implications Of the Tumor Macroenviromentmentioning
confidence: 99%
“…In children with high-risk NB, pulmonary metastases are crucial for the long-term outcome. In an orthotopic mouse model for human neuroblastoma metastases (Mhh-NB11 and SH-SY5Y), Maman et al 131 showed that lung-derived factors significantly reduced the viability of micro-NB cells by upregulating the expression of pro-apoptotic genes, inducing cell cycle arrest and decreasing ERK and FAK phosphorylation. The authors concluded that further insights into distant organ environment could reveal therapeutic options against NB metastases.…”
Section: Clinical Implications Of the Tumor Macroenviromentmentioning
confidence: 99%
“…More importantly, they found common genes combined specific genes were required for successful metastasis to each site while a single molecule hardly exerted effect, which suggested that inhibition of both common genes and specific genes decrease metastasis and offered a new direction for target different metastasis from a same disease. Witz's group also identified common genes and different genes for site-specific metastasis using the cell lines with an identical genetic background [160,161]. These studies give us an clue that searching for common molecules playing key roles in different metastases from a same cancer or the same organ metastasis from various cancers is a direction of simplicity to treat cancer metastasis.…”
Section: Unravelling the Complexity Of Metastasis-identify Common Plamentioning
confidence: 96%
“…The different genes may be regulated by site-specific microenvironment, which have been testified in experiment studies. For example, Massague's group and Witz's group isolated of different site specific metastatic cells from the same tumors through selection in targeted organs [124,[158][159][160][161]. There were common mediators to contribute to pulmonary and brain metastases.…”
Section: Hematogenous and Lymphatic Metastases Have Common And Differmentioning
confidence: 99%
“…Dormant micrometastasis could progress to an actively growing macrometastatic lesion and cause a late metastatic relapse in the high risk group of NBL patients [283]. Thus, specific microenvironment factors involved in the progression of micrometastasis or in the attraction of human neuroblastoma cells in the site of metastasis have been studied in several organs, such as lung [284], bone [285,286] or BM [287].…”
Section: Neuroblastoma Microenvironmentmentioning
confidence: 99%